Cost- and Delay-Efficient Backhaul Selection for Time-Sensitive Maritime Communications - Saafi, Salwa; Vikhrova, Olga; Fodor, Gabor; Hošek, Jiří; Andreev, Sergey (IEEE, 2023)
Extending the existing near-shore terrestrial infrastructure with non-terrestrial network capabilities helps maritime operators alleviate the high costs of communication and meet the requirements imposed by time-sensitive applications. Recognizing that the deployment of terrestrial and non-terrestrial networks necessitates selecting from the available wireless backhaul solutions, which have dissimilar data transmission costs and communication link qualities, it is essential to propose an appropriate backhaul selection policy. Specifically, in this letter, we coin a backhaul selection policy that manages the inherent trade-off between data transmission expenses and timely throughput guarantees for maritime communications. We formulate the backhaul selection problem as a Markov decision process and show that the proposed solution is not only more cost-efficient, but also satisfies the timely throughput requirements in contrast to currently used greedy strategies.

Extending the existing near-shore terrestrial infrastructure with non-terrestrial network capabilities helps maritime operators alleviate the high costs of communication and meet the requirements imposed by time-sensitive applications. Recognizing that the deployment of terrestrial and non-terrestrial networks necessitates selecting from the available wireless backhaul solutions, which have dissimilar data transmission costs and communication link qualities, it is essential to propose an appropriate backhaul selection policy. Specifically, in this letter, we coin a backhaul selection policy that manages the inherent trade-off between data transmission expenses and timely throughput guarantees for maritime communications. We formulate the backhaul selection problem as a Markov decision process and show that the proposed solution is not only more cost-efficient, but also satisfies the timely throughput requirements in contrast to currently used greedy strategies.
Cost- and Delay-Efficient Backhaul Selection for Time-Sensitive Maritime Communications
Keywords: Backhaul selection; cost efficiency; near-shore communications; non-terrestrial networks; timely throughput; Backhaul selection; cost efficiency; near-shore communications; non-terrestrial networks; timely throughput